TECHNICAL TERMS IN SOP OF QUALITY SYSTEM DOCUMENT AT PT. NOK ASIA BATAM:SEMANTIC ANALYSIS - Sardinatalia Purba; Febri Asnita Saragih (LINGUA LITERA : journal of english linguistics and literature, 2019)
Document is something tangible or evidence that records communication or facts with the help of marks, words, or symbols.Each company must have some documents, as in this research the writer analyze the technical terms in SOP document quality system document at PT. Nok Asia Batam. The writer using qualitative descriptive method because the data will be presented in the form of technical terms in research in PT. Nok Asia Batam and the writer analyzed the meaning of the technical terms according to the meaning of the SOP quality system document and according to the oxford dictionary of the technical terms will be analyzed based on Geoffrey Leech's theory of semantics that classifies the meaning into seven types: conceptual, connotative, effective, colocative, stylistic, reflective, and thematic.